Cu-Catalyzed Borylative and Silylative Transformations of Allenes: Use of β-Functionalized Allyl Copper Intermediates in Organic Synthesis - Fujihara, Tetsuaki; Tsuji, Yasushi (Synthesis, 2018)
Herein, copper-catalyzed borylative and silylative transformations of allenes using borylcopper or silylcopper as the active catalytic species are described. First, the synthesis and characterization of borylcopper and silylcopper complexes are briefly introduced. Next, the borylative transformations of allenes are summarized including hydroboration, carboboration, and borylative allylation of carbonyl compounds. We next deal with the silylative transformations of allenes such as hydrosilylation, carbosilylation, and silylative allylation of carbonyl compounds.1 Introduction2 Synthesis of Borylcopper and Silylcopper Complexes3 Borylative Transformations4 Silylative Transformations5 Conclusions and Future Outlook
Keywords: allene; allylcopper; borylation; silylation